2012
DOI: 10.1111/j.1537-2995.2012.03736.x
|View full text |Cite
|
Sign up to set email alerts
|

Two cases of transfusion‐transmitted hepatitis B virus (HBV) infection in a low‐endemic country before implementation of HBV nucleic acid testing

Abstract: The present cases highlight the importance of introducing highly sensitive HBV NAT to prevent transmission. Moreover, the lookback studies based on appropriate molecular and serologic investigations of patients transfused with previous donations from newly identified HBV-infected repeat donors offer the opportunity to treat a recently infected recipient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…The countries of the Americas and European are considered by the WHO to be of low prevalence for HBV [1]. Blood services estimated the residual risk before HBV-NAT ranging from 1: 62,500 to 1: 640,000 and after HBV-NAT ranging from 1: 115,000 to 1: 8,000,000 [15,27,28,29,30,31]. Considered by WHO as regions of medium and high prevalence of HBV infection, respectively, the Republic of Korea and the African continent described the RR before HBV-NAT between 1: 121 and 1: 1,000 and after HBV-NAT, Republic of Korea and the South Africa, between 1: 39,956 and 1: 43,666 [32,33,34,35,36,37].…”
Section: Discussionmentioning
confidence: 99%
“…The countries of the Americas and European are considered by the WHO to be of low prevalence for HBV [1]. Blood services estimated the residual risk before HBV-NAT ranging from 1: 62,500 to 1: 640,000 and after HBV-NAT ranging from 1: 115,000 to 1: 8,000,000 [15,27,28,29,30,31]. Considered by WHO as regions of medium and high prevalence of HBV infection, respectively, the Republic of Korea and the African continent described the RR before HBV-NAT between 1: 121 and 1: 1,000 and after HBV-NAT, Republic of Korea and the South Africa, between 1: 39,956 and 1: 43,666 [32,33,34,35,36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Seventeen of 24 HBV NAT DNA–positive but HBsAg‐negative samples had viral loads clearly less than 10 IU/mL. Blood products with these very low HBV viral loads are potentially infectious, as was shown in several recent reports . Which sensitivity limit should be implemented in future donor screening programs still needs to be determined in a controlled study; however, based on our observations, a theoretical sensitivity limit below 5 IU/mL must be achieved.…”
Section: Discussionmentioning
confidence: 57%
“…It has been demonstrated that HBV transfusion‐transmitted infections often occur from WP cases with very low viral loads often below the linear range of the detection assay (<5 IU/mL) . The risk of viral transmission, however, does not solely depend on the viral dose; other factors, such as the anti‐HBs status of the donor, the immune status of the recipient, and the amount of plasma transfused, equally play a vital role in the viral transmission .…”
Section: Discussionmentioning
confidence: 99%
“…The HBV residual risk was estimated at 1 : 640.000 for the 1992-2003 period, and the cost-effectiveness of HIV/HCV NAT was thought poor [42]. Before introduction of HBV NAT screening in 2010, the HBV residual risk was calculated as 1 : 1,886.792, with a lookback research confirming only two cases of HBV transmitted by blood transfusion [43].…”
Section: Developed Countriesmentioning
confidence: 99%